Analysis of the Implementation and Follow-Up Recommendations of Neonatal Maternal and Perinatal Audit Surveillance and Response (MPASR) - Sulicha Nurhayati; Martha Irene Kartasurya; Cahya Tri Purnami (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Neonatal mortality remains a critical barrier to achieving the Sustainable Development Goals (SDGs), particularly in District X, where deaths during the first 0–6 days of life are rising. This study explores the implementation of the Maternal Perinatal Audit Surveillance and Response (MPASR) policy at the hospital level and evaluates the extent to which its recommendations are followed to reduce preventable neonatal deaths. A descriptive qualitative case study was conducted in two referral hospitals (one public and one private) in District X. Twelve purposively selected informants directly involved in neonatal MPASR implementation participated in in-depth interviews. Data were triangulated through direct observation and document review, including perinatal medical records, neonatal mortality reports, MPASR policy documents, meeting minutes, and MPASR notification data. Thematic analysis was guided by the Van Meter and Van Horn policy implementation framework to identify factors influencing performance. Findings indicate that neonatal MPASR has been implemented in line with national guidelines, and all procedural stages (identification, reporting, audit, and response) are formally conducted. However, implementation remains inconsistent and unsustained. Gaps were observed in SOP adherence, human resource capacity, training continuity, and structured monitoring of recommendation follow-up. Communication across organizations is not standardized and often depends on key individuals. High clinical workload, limited financing, systemic constraints within the MPASR system, and administrative requirements of National Health Insurance contribute to reporting delays and weak execution of corrective actions. Although MPASR functions as a surveillance and audit mechanism, systemic weaknesses in follow-up and monitoring limit its effectiveness as an integrated quality improvement system, undermining its potential to reduce neonatal mortality and advance SDG targets. Strengthening integration with hospital quality systems, digitalizing reporting processes, establishing structured monitoring mechanisms, and reinforcing managerial and policy support are essential to optimize impact Keywords: MPASR, neonatal mortality, policy implementation